FEATURES OF PLANT EXTRACTS INFLUENCE ON THE KINETICS OF CUMENE OXIDATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
On the example of the model reaction of cumene oxidation herbal extracts are classified as antioxidants. It is established that according to the character of oxidation influence on the process, the extracts are divided into four major groups: 1) extracts, which function as conventional classic antioxidants, in the presence of these extracts on the kinetic curves of oxygen absorption, distinct induction periods appear; 2) extracts-moderators, in the presence of which kinetic curves of oxygen absorptions function without induction periods; 3) extracts, which operate as antioxidants at low concentrations and at relatively high concentrations, they undergo auto oxidation; 4) extracts, that inhibit the oxidation process to some extent. The mechanism of the effect of the extracts as antioxidants on the oxidation of cumene covering these groups is suggested.
Keywords: herbal antioxidants, classification, auto oxidation mechanism of activity, induction periods